Challenges and Pitfalls in the Engineering of Human Interleukin 22 (hIL-22) Secreting Lactobacillus reuteri - Ortiz-Velez, Laura; Goodwin, Annie; Schaefer, Laura; Britton, Robert A. (Frontiers in Bioengineering and Biotechnology, 2020)
Engineered microbes for the delivery of intestinally directed therapeutics is a promising avenue for the treatment of various intestinal diseases including inflammatory bowel disease (IBD) and intestinal graft vs. host disease (GVHD). This modality of treatment would allow for the targeted delivery of therapeutics to the site of inflammation or disease while minimizing the systemic side effects that often accompany treatment of these pathologies. Here, we show the challenges encountered and overcome in successfully engineering Lactobacillus reuteri to secrete high levels of biologically active human interleukin 22 (hIL-22). Initial hIL-22 constructs secreted high levels of hIL-22, however we found the majority of hIL-22 was cleaved and not biologically active. Several strategies were explored to improve the production of intact hIL-22, with the optimization of the signal sequence for peptide secretion having the most impact of production of intact hIL-22. This resulted in L. reuteri secreting high concentrations (up to 700 ng/mL) of hIL-22. Bioactivity of hIL-22 was confirmed by the secretion of interleukin 10 (IL-10) from the colon cancer derived epithelial cell line Colo205 and the secretion of Regenerating islet-derived protein 3 alpha (Reg3α) from human jejunal enteroids. The secretion of bioactive hIL-22 imposed a significant cost for L. reuteri as bacterial growth was significantly impaired upon induction. Future challenges and optimization strategies for the delivery of hIL-22 to the human intestinal tract are discussed.